Acetaldehyde as an Intermediate in the Electroreduction of Carbon Monoxide to Ethanol on Oxide‐Derived Copper. Issue 4 (21st December 2015) - Bertheussen, Erlend; Verdaguer‐Casadevall, Arnau; Ravasio, Davide; Montoya, Joseph H.; Trimarco, Daniel B.; Roy, Claudie; Meier, Sebastian; Wendland, Jürgen; Nørskov, Jens K.; Stephens, Ifan E. L.; Chorkendorff, Ib
Abstract: Oxide‐derived copper (OD‐Cu) electrodes exhibit unprecedented CO reduction performance towards liquid fuels, producing ethanol and acetate with >50 % Faradaic efficiency at −0.3 V (vs. RHE). By using static headspace‐gas chromatography for liquid phase analysis, we identify acetaldehyde as a minor product and key intermediate in the electroreduction of CO to ethanol on OD‐Cu electrodes. Acetaldehyde is produced with a Faradaic efficiency of ≈5 % at −0.33 V (vs. RHE). We show that acetaldehyde forms at low steady‐state concentrations, and that free acetaldehyde is difficult to detect in alkaline solutions using NMR spectroscopy, requiring alternative methods for detection and quantification. Our results represent an important step towards understanding the CO reduction mechanism on OD‐Cu electrodes. Abstract : An unappreciated intermediate : Acetaldehyde is identified as a product and key intermediate in CO reduction to ethanol on oxide‐derived copper. It is also shown that the detection of acetaldehyde with NMR spectroscopy in alkaline solution is challenging, requiring utilization of complementary techniques.